Toward Firm Performance in Indonesia: The Role of Good Corporate Governance and Investment Opportunity Set - Dedi Rusdi; Indri Kartika; Maya Indriastuti (Jurnal Economia, 2021)
Abstract: This study examined the role of good corporate governance and investment opportunity set in maintaining firm performance. This study's sample population comprised 240 manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2019. The research sample was selected using a purposive sampling method. The data were analyzed by using structural equation modeling analysis (SEM). The results showed that good corporate governance in terms of board size had a negative effect on firm performance. Meanwhile, good corporate governance in terms of board independence and investment opportunity set had a positive effect on firm performance.